Fruit Set dan Daya Simpan Buah Tanaman Cabai Rawit (Capsicum frutescens L.) Akibat Pemberian Paklobutrazol dan Pupuk Organik Cair Buah Pisang : Fruit Set and Fruit Shelf Life of Cayenne Pepper (Capsicum frutescens L.) Due to of Paclobutrazol and Banana Liquid Organic Fertilizer - Nova Triani; Agus Sulistyono (Agrocentrum, 2023)
Increasing the productivity of cayenne pepper (Capsicum frutescens L.) can be done through the use of growth regulators, namely paclobutrazol and liquid organic fertilizer. Treatment of paclobutrazol concentrations and doses of liquid organic fertilizer derived from banana fruit waste is expected to increase the fruit set and storability of the resulting cayenne pepper. The purpose of this study was to determine the best concentration of paclobutrazol and POC banana fruit to increase the fruit set of cayenne pepper, and to determine the best concentration of paclobutrazol to produce cayenne pepper with a more resistant shelf life. The research method used was using a Split Plot Design with the main plot being the dosage of liquid organic fertilizer for bananas, which consisted of NPK 40 g/plant (control), 300 ml/plant POC banana, 400 ml/plant and 500 ml/plant POC bananas. While the concentration of paclobutrazol as a sub-plot, which consisted of 0 ppm/without paclobutrazol (control), 100, 150 and 200 ppm. The results showed that there was a significant interaction between the combination treatment concentrations of paclobutrazol and the dosage of liquid organic fertilizer for bananas in the observed parameter of fruit set percentage. A higher percentage of fruit set was obtained from the combination treatment of 150 ppm paclobutrazol concentration with a dose of 300 ml/plant of banana liquid organic fertilizer. The concentration of paclobutrazol had a significant effect on the storability of cayenne pepper. Cayenne pepper that more resistant to storage were obtained from treatment with a concentration of 150 ppm paclobutrazol.